Profiles of economic constraints and marginalization among Korean working adults: differences in work and life outcomes - Lee, Seran; Yang, Hyunjung; Lee, Ki-Hak (Frontiers in Psychology, 2025)
IntroductionRecent research has explored profiles of economic constraints and marginalization based on the Psychology of Working Theory, but such investigations remain limited in Korea.MethodsThis study employed latent profile analysis to identify profiles of Korean working adults based on economic constraints and marginalization and examined their associations with demographic characteristics and job and life outcomes.ResultsAmong a sample of 481 Koreans, four distinct profiles emerged: privileged (38.5%), moderately marginalized (37.1%), economically constrained (14%), and disadvantaged (10.4%). The analysis revealed that individuals without a university degree were more likely to belong to the disadvantaged and economically constrained groups than to the privileged group, but no significant gender differences observed. Regarding job and life outcomes, the privileged group showed the highest levels of work volition, decent work, physical health, and life satisfaction. The moderately marginalized group exhibited lower levels than the privileged group. The economically constrained group demonstrated similar levels to the moderately marginalized group, except that life satisfaction and physical health were comparable to those of the disadvantaged group.DiscussionBased on these findings, theoretical and practical implications are discussed.